Réponses

Meilleure réponse !
2014-09-07T14:28:44+02:00
Bonjour

A = 1/5 x -4/3 + 7/2
A = -4/15 + 7/2 = - 8/30 + 105/30 = - 97/30

B = 4/5 : (-3/7) - 7/10
B = 4/5 x - 7/3 - 7/10
B = - 28/15 - 7/10
B = - 56/30 - 21/30 = - 77/30

C = 13/7 + ( -8/7) : (-4/5)
C = 13/7 + ( -8/7 x -5/4)
C = 13/7 + 40/28
C = 52/28 +40/28 = 92/28 =  23/7

D = 7/3 + 3/2 x -10/21
D = 7/3  + (- 30/42)
D = 7/3 - 30/42 = 98/42 -30/42 = 68/42 = 34/21

E = 13/7 + ( -8/7 ) ; ( - 4/5)
E = 13/7 + ( -8/7 x - 5/4)
E = 13/7 + 40/28
E = 13/7 + 10/7
E = 23/7

F = 6/5 - ( -1/9 x -3/4)
F = 6/5 - 3/36
F = 6/5 - 1/12
F = 72/60 - 5/60 = 67/60
l'exercice E c est pas le bon
oui tu as raison, j'ai fait 2 fois le C mais je pense que tu as compris la méthode